The hybrid model, and adaptive educational hypermedia frameworks - Zakaria, Mohamed Ramzy (2004)
The amount of information on the web is characterised by being enormous, as is the number of users with different goals and interests. User models have been utilized by adaptive hypermedia systems generally and adaptive educational hypermedia systems (AEHS) particularly to personalize the amount of information they have with respect to each individual's knowledge, background and goals. As a result of the research described herein, a user model called the Hybrid Model has been developed. This model is both generic and abstract, and it extends other models used by AEHS by measuring users' knowledge levels with respect to different knowledge domains simultaneously by utilising well known techniques in the world of user modelling, specifically the Overlay model (which has been modified) and the Stereotype model. Therefore, using the Hybrid Model, AEHS will not be restricted to a single knowledge domain at anyone time. Thus, by implementing the Hybrid model, those systems can manage users' knowledge globally with respect to the deployed knowledge domains. The model has been implemented experimentally in an educational hypermedia system called WHURLE (Web-based Hierarchal Universal Reactive Learning Environment) to verify its aim - managing users' knowledge globally. Moreover, this implementation has been tested successfully through a user trial as an adaptive revision guide for a Biological Anthropology Course. Furthermore, the infrastructure of the WHURLE system has been modified to embrace the objective of the Hybrid Model. This has led to a novel design that provides the system with the capability of utilising different user models easily without affecting any of its component modules.